The performance of politically connected firms in South East Europe: state capture or business capture? - Will Bartlett (London School of Economics and Political Science (LSE), European Institute, 2021)
This paper investigates the effects of the political connectedness of private sector firms in South East Europe on their business performance. This question is relevant to contemporary ideas about the importance of "state capture" in the region, and the paper provides a new perspective on the nature and consequences of this phenomenon. On the basis of evidence from empirical survey data as well as case study evidence, the paper concludes that political connections tend to undermine the business performance of the connected firms, with a potential negative impact on the economic development of the countries concerned. It is argued that this process is better described as "business capture" rather than "state capture". The terminology is important as it indicates the directions in which policy might be directed to effectively manage this issue and improve the competitiveness of economies in the region. The average overall negative effect on business performance measured by employment growth is substantial but is found to be statistically significant only the services sector and in countries of the Western Balkans. The EU member states of the region appear to be relatively immune from the negative effects of business capture.
Keywords: 330; Politically connected firms; state capture; Southeast Europe